ClimWood2030 - Climate benefits of material substitution by forest biomass and harvested wood products: Perspective 2030. Final report - Sebastian Rüter; Frank Werner; Nicklas Forsell; Christopher Prins; Estelle Vial; Anne-Laure Levet (Johann Heinrich von Thünen-Institut, 2016)
The ClimWood2030 study, commissioned by DG CLIMA of the European Commission, quantifies the five ways in which the EU forest sector contributes to climate change mitigation: carbon sequestration and storage in EU forests, carbon storage in harvested wood products in the EU, substitution of wood products for functionally equivalent materials and substitution of wood for other sources of energy, and displacement of emissions from forests outside the EU. It also explores through scenario analysis, based on a series of interlocking models (GLOBIOM, G4M and WoodCarbonMonitor), along with detailed analysis of Forest Based Functional Units, based on life cycle assessment (LCA), the consequences for GHG balances of policy choices at present under consideration. The focus is on the EU-28, but GHG balances for other parts of the world are also considered, notably to assess consequences of EU policy choices for other regions. The five scenarios are (I) The ClimWood2030 reference scenario, (II) Increase carbon stock in existing EU forests, (III) Cascade use - increase recovery of solid wood products, (IV) Cascade use - prevent first use of biomass for energy and (V) Strongly increase material wood use. The study presents detailed scenario results for key parameters, the policy instruments linked to the scenarios, and main conclusions. The ClimWood2030 study, commissioned by DG CLIMA of the European Commission, quantifies the five ways in which the EU forest sector contributes to climate change mitigation: carbon sequestration and storage in EU forests, carbon storage in harvested wood products in the EU, substitution of wood products for functionally equivalent materials and substitution of wood for other sources of energy, and displacement of emissions from forests outside the EU. It also explores through scenario analysis, based on a series of interlocking models (GLOBIOM, G4M and WoodCarbonMonitor), along with detailed analysis of Forest Based Functional Units, based on life cycle assessment (LCA), the consequences for GHG balances of policy choices at present under consideration. The focus is on the EU-28, but GHG balances for other parts of the world are also considered, notably to assess consequences of EU policy choices for other regions. The five scenarios are (I) The ClimWood2030 reference scenario, (II) Increase carbon stock in existing EU forests, (III) Cascade use - increase recovery of solid wood products, (IV) Cascade use - prevent first use of biomass for energy and (V) Strongly increase material wood use. The study presents detailed scenario results for key parameters, the policy instruments linked to the scenarios, and main conclusions.
urn:nbn:de:gbv:253-201607-dn056927-3
Keywords: 630; forest-based sector; climate change; greenhouse gas balance; harvested wood products; substitution; scenario analysis; policy instruments